Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\alpha$ and $\beta$ be two complex $(1,1)$ forms defined as:

$\alpha = \alpha_{ij} dx^i \wedge d\bar x^j$

$\beta= \beta_{ij} dx^i \wedge d\bar x^j$

Let's say, I know the following:

1) $\alpha \wedge \beta = 0$

2) $\beta \neq 0$

I want to somehow show that the only way to achieve (1) is by forcing $\alpha = 0$. Are there general known conditions on the $\beta_{ij}$ for this to happen?

The only condition I could think of is if all the $\beta_{ij}$ are the same. However, this is a bit too restrictive. I'm also interested in the above problem when $\beta$ is a $(2,2)$ form.

share|cite|improve this question
note that $dx^i\wedge dx^i = 0$ – user20266 Jun 23 '12 at 12:37
If you find an expression for the $\gamma$s (in terms of the $\alpha_{ij}$, $\beta_{ij}$ of cause) in e.g. $\alpha\wedge\beta = \sum_{i<k,j<l} \gamma_{ijkl} dx^i\wedge dx^k\wedge d\overline{x}^j \wedge d\overline{x}^l$, you will have a condition for the product to vanish, namely all the $\gamma_{ijkl}$ must vanish, by the uniqueness of this representation. – Ben Jun 23 '12 at 15:03
I believe my question might have been misunderstood due to the title (which I chose for shortness). I have rephrased it to reflect the actual question – FMN Jun 24 '12 at 13:25

\begin{eqnarray} \alpha\wedge\beta &=&\sum_{i,j,k,l}\alpha_{ij}\beta_{kl}dx^i\wedge d\bar{x}^j\wedge dx^k\wedge d\bar{x}^l\cr &=&(\sum_{i<k,j<l}+\sum_{i<k,l<j}+\sum_{k<i,j<l}+\sum_{k<i,l<j})\alpha_{ij}\beta_{kl}dx^i\wedge d\bar{x}^j\wedge dx^k\wedge d\bar{x}^l\cr &=&\sum_{i<k,j<l}(-\alpha_{ij}\beta_{kl}+\alpha_{kj}\beta_{il}+\alpha_{il}\beta_{kj}- \alpha_{kl}\beta_{ij})dx^i\wedge dx^k\wedge d\bar{x}^j\wedge d\bar{x}^l. \end{eqnarray} Thus $$ \alpha\wedge\beta=0 \iff \alpha_{ij}\beta_{kl}+ \alpha_{kl}\beta_{ij}=\alpha_{kj}\beta_{il}+\alpha_{il}\beta_{kj} \quad \forall \ i<k,j<l. $$

share|cite|improve this answer
How about $(dx^1\wedge d\overline{x}^1 - dx^2\wedge d\overline{x}^2)\wedge(dx^1\wedge d\overline{x}^1 + dx^2\wedge d\overline{x}^2) = 0$? – Ben Jun 23 '12 at 14:52
@BenA.You're right. I just modified my previous statement. – Mercy King Jun 23 '12 at 20:47
There is something wrong in the last equation (it is not linear in the betas) – Mariano Suárez-Alvarez Jun 23 '12 at 21:21
What do you mean by "not linear in the $\beta$"? – Mercy King Jun 23 '12 at 21:25
@Mercy In the final expression, the $\beta_{kj}$ belongs to the $\alpha_{il}$ at the end. – Ben Jun 24 '12 at 9:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.